Enervări sau despre bucuria de a trăi în România - Bănică, Mirel 1971-; Constantinescu, Codruţ ca. 20./21. Jh (Polirom, 2007)
Compilation of the messages sent on postcards between Bănică and Constantinescu over a period of 10 months. Each message contained some tidbit about the joys or in some instances, the irritations of living in Romania
Keywords: Bănică, Mirel / Correspondence; Constantinescu, Codruț / Correspondence; Bănică, Mirel -- Correspondence; Constantinescu, Codruț -- Correspondence; Geschichte 2005-2006; Alltag, Brauchtum; Politik; Zeitfragen; Romania / Social life and customs / 21st century; Romania / Politics and government / 21st century; Rumänien; Romania -- Politics and government -- 21st century; Romania -- Social life and customs -- 21st century